Moving and Moving Forward:: Mushuau Innu Relocation from Davis Inlet to Natuashish - Burns, Auŝra (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2006)
Abstract This paper draws upon the author's participatory research and community development work conducted over a four-year period (2001-2005) as a member of a capacity-building team established to support the relocation of the Mushuau Innu of Labrador from Davis Inlet to the new community of Natuashish in 2002-2003. Particular attention is devoted to the challenges faced by the Natuashish Housing Authority, which was assigned the task of implementing policies with respect to the new housing. The paper concludes with an assessment of the impact of the relocation on the Mushuau Innu community and the lessons learned from the experience.